The modified taungya system in Ghana’s transitional zone - Kalame, F.B. (2009)
This article is based on a study conducted in communities in three forest reserves in the offinso Forest District, which crosses the ashanti and brong-ahafo regions of Ghana. These communities include adaa, in opro forest reserve; nkwaankwaa and asempaneye, in afram forest reserve; and anhwerekrom in asufuo forest reserve. The brong-ahafo region is located between the central and northern parts of Ghana. in this transition zone, forest is quickly becoming wooded lands due to climatic factors such as increasing temperatures and decreasing precipitation, which result in frequent forest fires and drought events. non-climate drivers include increasing deforestation activities — logging, charcoal production, expansion of agricultural lands and mining activities — which leads to forest degradation and desertification. ashanti region has more degraded forest, although reforestation activities under mTs have slowed the gradual but constant southward change in vegetation from forest to wooded lands.